Role of CT colonoscopy for colorectal cancer screening in Indian population - Vedula RKR (Journal of Medical and Scientific Research, 2016)
Cancer as a cause of death is missed mostly in many parts of India. Mortality continues to rise from colorectal cancers that could well be prevented. Genetic, familial and dietary factors significantly account for increased risk of colorectal cancers. More so, large bowel origin of cancer, as a primary lesion or a source of distant metastases is undetected in a large number of patients in the absence of a complete work up. Even with metastatic disease, patients with colorectal cancer survive for many years unlike those having upper gastrointestinal cancers. Colorectal malignancy is potentially curable if detected early by several established screening methods. Today there is a range of options for CRC screening in the average-risk population, with current technology falling into 2 general categories: stool tests, which include tests for occult blood or exfoliated DNA; and structural exams, which include flexible sigmoidoscopy (FSIG), colonoscopy, double-contrast barium enema (DCBE) and computed tomographic colonography (CTC). Any one of these options applied in a systematic program of regular screening has the potential to significantly reduce deaths from CRC. Computerized tomographic scanning colonoscopy (CTC) is the least invasive outpatient procedure and not well recognized in India as a screening tool. CTC is a minimally invasive imaging examination of the entire colon and rectum and uses Multi detector CT scanner to acquire images and advanced 2-dimensional (2D) and 3-dimensional (3D)-image display techniques for interpretation. Clinical trials including large cohorts studies of CTC yielded promising results and paved the way for larger multicenter screening trials. CTC sensitivity and specificity for large (10 mm) polyps was found to be as high as 85% to 93% and 97% respectively. The majority of studies assessing the relative acceptability of CTC and conventional colonoscopy in patients who have undergone both tests on the same day have demonstrated a preference for CTC. Screening of average-risk adults with CTC should commence at age 50 years though the interval for repeat examination after a negative CTC has not been studied. However, screening may be limited to select groups in India because of our own limitations.